2021
DOI: 10.1177/09713557211025655
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entrepreneurial Finance in Corporate Social Responsibility and New Venture Performance in an Emerging Market

Abstract: Corporate social responsibility (CSR) has over the past decades transformed from a philanthropic attribute to something compulsory. It has become the imperative duty of organisations, irrespective of their size, nature of business and age. However, because of poor financial capabilities and lack of support, newly established ventures too often fail to voluntarily participate in social and environmental activities. This is one reason why national governments have initiated various programs and policies to encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 104 publications
(173 reference statements)
2
14
0
1
Order By: Relevance
“…The findings are similar to the results by (Aterido et al, 2012) that monetary services are vital to the economic progress and the growth of Small and medium enterprises, and their availability is linked to productivity and performance. The results are reliable to those of Khattak et al (2021) who found that access to financial services improves business performance. The results revealed that training services (β =0.236, p=0.004<.05) had a positive and significant effect on the performance of a youthowned enterprise.…”
Section: Findings and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The findings are similar to the results by (Aterido et al, 2012) that monetary services are vital to the economic progress and the growth of Small and medium enterprises, and their availability is linked to productivity and performance. The results are reliable to those of Khattak et al (2021) who found that access to financial services improves business performance. The results revealed that training services (β =0.236, p=0.004<.05) had a positive and significant effect on the performance of a youthowned enterprise.…”
Section: Findings and Discussionsupporting
confidence: 81%
“…The study used basic descriptive data to demonstrate how microfinance helped young people acquire microloans, develop their wealth by opening or expanding enterprises, and ultimately find employment. Khattak et al (2021), the government should support financial institutions that extend credit, especially to budding enterprises, the research suggests. The poll did not, however, ask young business owners if they are aware of readily available financial services or whether they are aware of the restrictions that banks have before giving loans.…”
Section: Financial Services and Performance Of Youth-owned Enterprisesmentioning
confidence: 99%
“…Our research confirmed that both types of finance-domestic and international-are necessary for high sustainability performance. Similarly, a recent study conducted by Khattak et al (2021) indicates that entrepreneurial finance is the key to CSR and environmental activities in newly established ventures.…”
Section: Discussionmentioning
confidence: 90%
“…Finance is a key to sustainability activities and sustainable reporting (Naidoo 2020); subsequently, SMEs with sufficient financial resources easily practice green activities and environmental initiatives (Khan et al 2021a). When enterprises have sufficient finances, they easily perform CSR activities (Khattak et al 2021). However, SMEs sometimes have lack adequate financing which hinders them from investing in social activities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Regarding firm level attributes, there have been heterogeneous results. For instance, some studies have found that large enterprises and mature enterprises have formal strategies for social responsibility (Jin et al, 2019; Withisuphakorn & Jiraporn, 2016), while others Khattak et al (2021), Ullah et al (2022) state that newly established ventures are more likely to actively emphasize environmental practices.…”
Section: Introductionmentioning
confidence: 99%